Analisis Dan Perancangan Sistem Informasi Akuntansi Penjualan, Piutang Dan Penerimaan Kas (Studi Kasus pada UD.Praktis di Magetan) - Roro Suprantiningrum (FEB UNTAG Semarang, 2016)
AbstractThis study aimed to analyze the accounting records and then perform the design of information systems related to Sales, Accounts Receivable and Cash Receipts on UD.Praktis in Magetan, East Java. The research method used is descriptive analysis method and design that uses an object-oriented approach he designed the Accounting Information Systems Sales, Accounts Receivable and Cash Receipts are expected to be useful for the management of the company as the provision of information that is easier and more complete.Research results show that UD.Praktis a commercial enterprise engaged in the craft of skin that have some problems, namely: The information technology is not maximized as accounting records that are still manual, not the part that handles the collection of accounts receivable, still the geminating task in which part of the succession interfere in another part task. With dibangunya accounting information system that regulates Sales, Accounts Receivable and Cash Receipts company, it is expected to help the company to conduct operations and internal controls such as the roles and responsibilities of employees, generate accurate information and reports so that it can support in corporate decision.Keywords: Accounting Information Systems, Credit Sales, Accounts Receivable, Cash Receipts